THE EFFECT OF JOB SATISFACTION TOWARD HEALTH WORKER'S SERVICE QUALITY OF VILLAGE HEALTH COTTAGE IN SITUBONDO DISTRICT - Andayani, Kartika Sari; Sugiyanta; Iqbal, Muhammad (Universitas Airlangga, 2024)
Introduction: The quality of health worker services is an important parameter to increase the pace of health development. The decline in the quality of health worker services was caused by a decrease in the job satisfaction of health workers. Based on the report on standardization of the quality of Ponkesdes services at the Situbondo District Health Office (2020), the number of Ponkesdes that received the title of